THE INTERNAL CONTROL AS A METHOD OF MANAGING THE FINANCIAL STABILITY OF A COMPANY IN A VOLATILE ECONOMIC ENVIRONMENT - Y. Y. Fayantseva (Финансы: теория и практика)
The in-house control of the financial stability of companies in the volatile economic environment is an effective tool for making managerial decisions. The instability and turbulence of the environment make it impossible to use traditional theories for this purpose. To overcome this problem, the article presents the author’s method of an improved paradigm of the internal control over the financial stability of an enterprise under the conditions of economic instability. The proposed conceptual approach reflects the order and conditions of carrying out the internal control as well as the procedure for making managerial decisions based on its results. To formalize the control, a control system card is proposed as an administrative document of a production enterprise that contains the description of the main components of the enterprise activity control system and its individual subsystems.